Analysis of Court Decision Rejecting Homologation of the Settlement Proposal Approved by Creditors in the Process of Postponing Payment Obligations - Nurwati; Gustini, Rucita; Sihotang, Sudiman (DE'RECHTSSTAAT, 2025)
Postponement of Debt Payment Obligations (PKPU) is an important legal instrument in the Indonesian bankruptcy legal system regulated in Law Number 37 of 2004 concerning Bankruptcy and PKPU. Ideally, PKPU is designed to provide debtors with the opportunity to restructure debts and reach agreements with their creditors through a peace process, with the aim of running the business and optimal debt repayment to creditors. However, in practice, even though the majority of creditors agree to the peace proposal submitted by the debtor, the Commercial Court has the authority to reject the peace agreement or homologation based on certain legal considerations. The purpose of this study is to examine the peace process in the Postponement of Debt Payment Obligations (PKPU) between debtors and creditors, with a particular focus on the requirements and regulations required to obtain approval from the Commercial Court, as well as to examine the impact of rejecting the approval of the peace proposal that has been approved. The study uses a statutory approach and a case approach to examine aspects of the PKPU peace process. The results of the study reveal that the peace agreement by the Commercial Court does not only depend on the approval of creditors but must also comply with the conditions set. Rejection of ratification by the court can result in the debtor being declared bankrupt by law, where this causes the management of the debtor's assets to be transferred to the curator for settlement. This impact not only affects the continuity of the debtor's business but also has the potential to reduce the level of debt repayment to creditors.